2014
DOI: 10.1542/peds.2013-4257
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Provision of Adolescent Vaccines in Primary Care: A Randomized Controlled Trial

Abstract: WHAT'S KNOWN ON THIS SUBJECT: The Centers for Disease Control and Prevention recommends that health departments in all 50 states deliver AFIX (Assessment, Feedback, Incentives, and eXchange) consultations to 25% of federally funded vaccine providers each year. AFIX effectively raises vaccination coverage among young children.WHAT THIS STUDY ADDS: AFIX consultations achieved short-term gains in coverage for 11-to 12-year-olds for vaccines in the adolescent platform. No gains occurred for older adolescents or ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 7 publications
2
93
0
Order By: Relevance
“…A follow-up study included 91 primary care clinics that were randomized to receive an in-person AFIX consultation, a virtual AFIX consultation, or no consultation. 88 At the 5-month follow-up assessment, it was found that the in person and virtual AFIX consultations were equally effective for improving adolescent vaccination, and both were better than no consultation. The impact of AFIX was greatest for younger adolescents, with vaccination levels among 11-12-year-olds 1.5%-4.7% higher in either AFIX arm (depending on the vaccine assessed) when compared with the control arm.…”
Section: P=002)mentioning
confidence: 97%
“…A follow-up study included 91 primary care clinics that were randomized to receive an in-person AFIX consultation, a virtual AFIX consultation, or no consultation. 88 At the 5-month follow-up assessment, it was found that the in person and virtual AFIX consultations were equally effective for improving adolescent vaccination, and both were better than no consultation. The impact of AFIX was greatest for younger adolescents, with vaccination levels among 11-12-year-olds 1.5%-4.7% higher in either AFIX arm (depending on the vaccine assessed) when compared with the control arm.…”
Section: P=002)mentioning
confidence: 97%
“…HPV completion rates were highest among clinics that received an in-person AFIX consult. 38 Both authors commented on the high level of acceptability of the intervention by key stakeholders. Moss et al observed a small but statistically significant increase in series completion rates after a 1-time AFIX consultation over 1 month.…”
Section: Behavioral Interventions: Providertargeted Interventions (N mentioning
confidence: 99%
“…In a randomized controlled trial in North Carolina, AFIX improved immunization rates in 11-through 12-year-old adolescents by 3 to 4 percentage points for Tdap vaccine, by 4 to 5 percentage points for meningococcal vaccine, and by 2 percentage points for HPV vaccine initiation. 80 AFIX has highlighted that actual immunization rates in a practice might not mirror clinicians' perceptions of vaccine administration within their practice. To monitor immunization rates, a practice may periodically audit a sample of their patients.…”
Section: The Role Of Aap Chapters and The Cdcmentioning
confidence: 99%